Maximum movies--pulp fictions : film culture and the worlds of Samuel Fuller, Mickey Spillane, and Jim Thompson - Stanfield, Peter, 1958- (Rutgers University Press, 2011)
Maximum Movies--Pulp Fictions describes two worlds. One of these worlds comprises a clutch of noisy, garish pulp movies, pumped out for the grind houses at the end of the urban exhibition chain by the studios' B-divisions and fly-by-night independents. The other is occupied by critics, intellectuals, cinephiles, and filmmakers who championed the cause of these movies. Against the legitimate, and in defense of the illegitimate, in an insolent and unruly manner, they agitated for the recognition of lurid sensational crime stories, war pictures, fast-paced Westerns, thrillers, and gangste.